MOTIVASI KERJA GURU DALAM MELAKSANAKAN TUGAS DI SMP NEGERI 1 KECAMATAN GUGUAK KABUPATEN LIMA PULUH KOTA - Mona Silvia (Jurnal Bahana Manajemen Pendidikan, 2013)
This research is motivated by the lack of motivation of teachers SMP Negeri 1 Guguak District District Fifty Cities in performing the task. This is a descriptive study, the study population was all teachers in junior high. The research instrument was a questionnaire Likert scale models that have been tested for validity and reliability, and analyzed using the average formula. This study shows that the motivation of teachers in SMP Negeri 1 sub guguak high category, but needs to be improved in order to better achieve educational goals well. Kata kunci: motivasi kerja